Peran Literasi Digital dalam Pengembangan Kompetensi Calon Guru Sekolah Dasar - Silvy Nur A; Siska Afriyanti A; Wafda Aufa A; Wuli Oktiningrum (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This qualitative study investigates the role of digital literacy in developing the competencies of prospective elementary school (SD) teachers in Indonesia. Literature studies show that teacher competencies, encompassing pedagogical, personality, social, and professional aspects, are crucial and influenced by various factors, including digital literacy. The digital literacy gap among SD teachers is attributed to a lack of technology-integrated training, infrastructure disparities, insufficient motivation and support, lack of self-confidence, and low awareness of the importance of digital literacy. This research highlights the importance of enhancing the digital literacy of prospective SD teachers to support their competencies. Proposed strategies include integrating digital literacy into the curriculum, practice-based training, enhancing lecturer competencies, developing a campus digital ecosystem, collaborating with industry, and implementing digital-based evaluations. In conclusion, improving the digital literacy of prospective SD teachers is a crucial step in enhancing the quality of education in Indonesia.